Hormone receptor activities of complex mixtures of known and suspect chemicals in personal silicone wristband samplers worn in office buildings. (February 2023) - Young, Anna S.; Herkert, Nicholas; Stapleton, Heather M.; Coull, Brent A.; Hauser, Russ; Zoeller, Thomas; Behnisch, Peter A.; Felzel, Emiel; Brouwer, Abraham; Allen, Joseph G.
Abstract: Humans are exposed to increasingly complex mixtures of hormone-disrupting chemicals from a variety of sources, yet, traditional research methods only evaluate a small number of chemicals at a time. We aimed to advance novel methods to investigate exposures to complex chemical mixtures. Silicone wristbands were worn by 243 office workers in the USA, UK, China, and India during four work shifts. We analyzed extracts of the wristbands for: 1) 99 known (targeted) chemicals; 2) 1000+ unknown chemical features, tentatively identified through suspect screening; and 3) total hormonal activities towards estrogen (ER), androgen (AR), and thyroid hormone (TR) receptors in human cell assays. We evaluated associations of chemicals with hormonal activities using Bayesian kernel machine regression models, separately for targeted versus suspect chemicals (with detection ≥50%). Every wristband exhibited hormonal activity towards at least one receptor: 99% antagonized TR, 96% antagonized AR, and 58% agonized ER. Compared to men, women were exposed to mixtures that were more estrogenic (180% higher, adjusted for country, age, and skin oil abundance in wristband), anti-androgenic (110% higher), and complex (median 836 detected chemical features versus 780). Adjusted models showed strong associations of jointly increasing chemical concentrations with higher hormonal activities. Several targeted and suspect chemicals were important co-drivers of overall mixture effects, including chemicals used as plasticizers, fragrance, sunscreen, pesticides, and from other or unknown sources. This study highlights the role of personal care products and building microenvironments in hormone-disrupting exposures, and the substantial contribution of chemicals not often identifiable or well-understood to those exposures. Graphical abstract: Image 1 Highlights: Office workers wore silicone wristbands to collect exposures to chemical mixtures. We observed 1044 chemical signatures in wristband samples via suspect screening. Every wristband extract was hormonally active in human hormone receptor cell assays. The chemical mixtures disrupted estrogen, androgen, and thyroid hormone receptors. Exposures were influenced by personal care products, buildings, gender disparities.